SAE8620H steel tail end hardenability detection method
By adding nitrogen gas to the heat treatment furnace of SAE8620H steel and performing water spray quenching, the problem of poor consistency of detection values is solved, the accuracy and consistency of detection values are improved, and the accurate evaluation of steel performance and product reliability are ensured.
Patent Information
- Application Number
- CN202411151822.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-02-14
AI Technical Summary
The detection value consistency of the existing SAE8620H steel end hardenability detection method is poor, which affects the accurate evaluation of steel performance.
The entire furnace is covered by adding nitrogen to the heat treatment furnace, heating the sample to the austenitization temperature and then quenching it by spraying water, and using a stable water temperature during cooling, the hardness of the quenching end is measured.
It improves the consistency and accuracy of the end hardenability detection value of SAE8620H steel, ensures the consistency of the mechanical properties and quality of the steel, improves the reliability of the product, and reduces the defective rate and rework rate.
Smart Images

Figure CN119437955A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material performance testing, in particular to a method for detecting the end hardenability of SAE8620H steel. Background Art
[0002] In modern industrial production, especially in the automotive industry, the application performance of gear steel has a decisive influence on the quality and life of the product. As a common carburized gear steel, the hardenability of SAE8620H steel is one of the key parameters for evaluating and controlling the performance of steel. Hardenability refers to the ability of steel to form martensite during the quenching process, which is directly related to the hardness, strength and toughness of gears and other parts.
[0003] At present, the detection of hardenability mainly relies on the end quenching test method. However, in actual application, this method has the problems of exposing the sample to the air and the furnace, contacting other gases in the furnace or contacting the vaporized residual quenching oil to produce chemical reactions, and the unstable water flow during water spraying affecting the abnormal values of each point, resulting in instability, resulting in poor consistency of the test values, and affecting the accurate evaluation of steel performance.
[0004] The disclosure of the above background technology content is only used to assist in understanding the concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed on the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention
[0005] The present application provides a method for detecting the end hardenability of SAE8620H steel, which is used to solve the problem of poor consistency of detection values of the hardenability detection method in the related art.
[0006] To achieve the above-mentioned purpose, the embodiment of the present application discloses the following technical solution: a method for detecting the end hardenability of SAE8620H steel, comprising the following steps:
[0007] Prepare the test specimen;
[0008] Placing the sample in a heat treatment furnace, adding nitrogen into the heat treatment furnace, wherein the nitrogen covers the entire furnace of the heat treatment furnace, and heating the sample to an austenitizing temperature;
[0009] After the holding time is over, the sample is taken out from the heating furnace and subjected to water spray quenching;
[0010] After quenching, the sample is placed in water for cooling;
[0011] After the sample is cooled, the hardness of the quenched end of the sample is measured.
[0012] In the embodiment of the present application, by adding nitrogen to cover the entire furnace, the oxygen content in the furnace of the heat treatment furnace can be greatly reduced, so that the steel sample is not prone to oxidation reaction at high temperature. In addition, the good thermal diffusivity of nitrogen can form a uniform atmosphere in the furnace, avoiding the unevenness of local gas composition and temperature. In addition, the introduction of nitrogen can form a positive pressure environment, preventing the infiltration of outside air, and further protecting the stability of the atmosphere in the furnace. In this way, it can be ensured that the chemical composition and heating of the sample during the heating and insulation process are more uniform and stable, so that the consistency and accuracy of the SAE8620H steel end hardenability test value (hardness measurement) can be improved, which is conducive to improving the calculation accuracy of the mathematical model and meeting the SAE8620H steel hardenability calculation requirements; ensure that each batch of steel produced has consistent mechanical properties and quality, improve product reliability, reduce defective rate and rework rate, reduce scrapping due to quality problems, and save production costs and time. In addition, it can also reduce trial and error costs and improve production efficiency.
[0013] In some possible implementations, the step of placing the sample in a heat treatment furnace includes: placing one end of the sample in a sleeve; adding carbon powder into the sleeve, wherein the amount of carbon powder added is 1 / 7-1 / 5 of the volume of the sleeve; placing the sleeve in the heat treatment furnace;
[0014] The method of water-spray quenching the sample is to spray water quench one end of the sample placed in the sleeve. In this way, the end of the sample to be quenched can be protected by the carbon powder in the sleeve to prevent oxidation and adhesion of the end of the sample, thereby improving the accuracy and consistency of the hardness measurement of the quenched end of the sample.
[0015] In some possible implementations, the amount of carbon powder added to the sleeve is 1 / 6 of the volume of the sleeve.
[0016] In some possible implementations, the spray water flow rate used for water spray quenching is in the range of 1L-2L / min, and the spray time is in the range of 649 seconds-671 seconds. In this way, the temperature distribution during the quenching process can be optimized to ensure that the sample is cooled evenly and appropriately during the quenching process, thereby avoiding the quenching cracks or uneven hardness caused by the thermal shock effect, and further improving the accuracy and consistency of the hardness measurement of the quenched end of the sample.
[0017] In some possible implementations, the spray water flow rate used for water spray quenching is 2 L / min, and the water spray time is 660 seconds.
[0018] In some possible implementations, the sample is quenched by water spraying within 0-5 seconds after the end of the holding time, so as to reduce the influence of temperature fluctuation on the hardness measurement, thereby improving the accuracy and consistency of the hardness measurement of the quenched end of the sample.
[0019] In some possible implementations, the method of heating the sample to the austenitizing temperature is: heating the heat treatment furnace to 920°C-930°C for a heating time range of 18-22 minutes; when the temperature in the heat treatment furnace reaches 920°C to 930°C, the sample is kept warm for a heating time range of 28-32 minutes. In this way, it is ensured that the sample is completely transformed at the austenitizing temperature.
[0020] In some possible implementations, the temperature of the heat treatment furnace is 925° C., the heating time of the heat treatment furnace is 20 minutes, and the keeping time of the heat treatment furnace is 30 minutes.
[0021] In some possible implementations, the temperature of the water used for cooling the sample is in the range of 20°C to 25°C.
[0022] In some possible embodiments, the step of measuring the hardness of the quenched end of the sample includes: grinding a measuring plane on the surface of the sample along the axial direction of the sample; and measuring the hardness on the measuring plane at preset intervals from the quenched end to the non-quenched end along the axial direction of the sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic flow chart of a method for detecting the end hardenability of SAE8620H steel provided in some embodiments of the present application. DETAILED DESCRIPTION
[0024] Specific embodiments of the present invention will now be mentioned in detail. Although the present invention is described in conjunction with these specific embodiments, it should be appreciated that it is not intended to limit the present invention to these specific embodiments. On the contrary, these embodiments are intended to cover substitutions, changes or equivalent embodiments that may be included in the spirit and scope of the invention defined by the claims. In the following description, a large number of specific details are set forth in order to provide a comprehensive understanding of the present invention. The present invention can be implemented without some or all of these specific details. In other cases, in order not to make the present invention unnecessarily obscure, well-known process operations are not described in detail.
[0025] When used in conjunction with "including," "methods comprising," or similar language in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0026] In modern industrial production, especially in the automotive industry, the application performance of gear steel has a decisive influence on the quality and life of the product. As a common carburized gear steel, the hardenability of SAE8620H steel is one of the key parameters for evaluating and controlling the performance of steel. Hardenability refers to the ability of steel to form martensite during the quenching process, which is directly related to the hardness, strength and toughness of gears and other parts.
[0027] At present, the detection of hardenability mainly relies on the end quenching test method. However, in actual application, this method has the problems of exposing the sample to the air and the furnace, contacting other gases in the furnace or contacting the vaporized residual quenching oil to produce chemical reactions, and the unstable water flow during water spraying affecting the abnormal values of each point, resulting in instability, resulting in poor consistency of the test values, and affecting the accurate evaluation of steel performance.
[0028] For details, please refer to the following Tables 1 and 2, wherein Table 1 is the hardenability requirements specified in GB / T225. Table 2 is the Rockwell hardness test data obtained by the end quenching test method.
[0029] Table 1
[0030]
[0031] Table 2
[0032]
[0033] By comparing Table 1 and Table 2, it can be seen that the consistency of the test values of the end quenching test method is poor, and some data exceed the standard range.
[0034] To solve the above technical problems, please refer to Figure 1 The present application embodiment provides a method for detecting the end hardenability of SAE8620H steel, comprising the following steps:
[0035] S100: prepare sample;
[0036] S200: placing the sample in a heat treatment furnace, adding nitrogen into the heat treatment furnace, wherein the nitrogen covers the entire furnace of the heat treatment furnace, and heating the sample to an austenitizing temperature;
[0037] Specifically, the heat treatment furnace may be a controlled atmosphere heat treatment furnace or a metal container with a small amount of granular graphite or cast iron chips placed at the bottom of the container and arranged at a uniform temperature in the furnace.
[0038] S300: After the holding time is over, the sample is taken out of the heating furnace and subjected to water spray quenching;
[0039] S400: After quenching, the sample is placed in water for cooling;
[0040] S500: After the sample is cooled, the hardness of the quenched end of the sample is measured.
[0041] Among them, by adding nitrogen to cover the entire furnace, the oxygen content in the heat treatment furnace can be greatly reduced, making it difficult for the steel sample to undergo oxidation reaction at high temperature. In addition, the good thermal diffusivity of nitrogen can form a uniform atmosphere in the furnace, avoiding local gas composition and temperature unevenness. In addition, the introduction of nitrogen can form a positive pressure environment, preventing the infiltration of outside air and further protecting the stability of the atmosphere in the furnace. In this way, it can ensure that the chemical composition and heat of the sample during the heating and insulation process are more uniform and stable, thereby improving the consistency and accuracy of the SAE8620H steel end hardenability test value (hardness measurement), effectively solving the problem of poor consistency of the test value of the end quenching test method, and further bringing about an accurate evaluation of the performance of the steel.
[0042] Preferably, in step S200, the step of placing the sample in a heat treatment furnace comprises: placing one end of the sample in a sleeve; adding carbon powder into the sleeve, wherein the amount of carbon powder added is 1 / 7-1 / 5 of the volume of the sleeve; placing the sleeve in the heat treatment furnace;
[0043] In step 300, the sample is subjected to water quenching by water quenching at one end of the sample placed in the sleeve. In this way, the end of the sample to be quenched can be protected by the carbon powder in the sleeve to prevent oxidation and adhesion of the end of the sample, thereby improving the accuracy and consistency of the hardness measurement of the quenched end of the sample. Specifically, the sleeve is made of a refractory heat-insulating material whose system performance indicators meet the relevant provisions of JGT 283-2010. Exemplarily, the refractory heat-insulating material can be aluminum silicate or ceramic fiber.
[0044] Furthermore, the amount of carbon powder added to the sleeve is 1 / 6 of the volume of the sleeve.
[0045] Preferably, in step S200, the method of heating the sample to the austenitizing temperature is: heating the heat treatment furnace to 920°C-930°C for a heating time range of 18-22 minutes; when the temperature in the heat treatment furnace reaches 920°C to 930°C, the sample is kept warm for a heating time range of 28-32 minutes. In this way, it can be ensured that the sample is completely transformed at the austenitizing temperature.
[0046] Furthermore, the temperature of the heat treatment furnace is 925° C., the heating time of the heat treatment furnace is 20 minutes, and the keeping time of the heat treatment furnace is 30 minutes.
[0047] Preferably, in step S300, the sample is quenched by water spraying within 0-5 seconds after the end of the holding time. In this way, the influence of temperature fluctuation on hardness measurement can be reduced, thereby improving the accuracy and consistency of hardness measurement at the quenched end of the sample.
[0048] Preferably, in step S300, the spray water flow rate used for water quenching is in the range of 1L-2L / min, and the spray time is in the range of 649 seconds-671 seconds. In this way, the temperature distribution during the quenching process can be optimized to ensure that the sample is cooled evenly and appropriately during the quenching process, thereby avoiding quenching cracks or uneven hardness caused by thermal shock effects, and further improving the accuracy and consistency of the hardness measurement of the quenched end of the sample.
[0049] Furthermore, the spray water flow rate used for water spray quenching is 2 L / min, and the water spray time is 660 seconds.
[0050] Preferably, in step S400, the temperature range of the water used for cooling the sample is 20°C-25°C.
[0051] Preferably, in step S500, the step of measuring the hardness of the quenched end of the sample includes: grinding a measuring plane on the surface of the sample along the axial direction of the sample; and measuring the hardness on the measuring plane at preset intervals from the quenched end to the non-quenched end along the axial direction of the sample.
[0052] Embodiment 1:
[0053] Preparation of test specimens:
[0054] The specification of SAE8620H gear steel is selected with a diameter of 60 mm to 125 mm; it is processed according to the following process steps: first, converter; second, LF+VD; third, continuous casting; fourth, rolling; fifth, finishing. Sampling is carried out according to the end quenching test method GB / T225-06 for steel hardenability proposed by my country.
[0055] Sample heating:
[0056] Place one end of the sample in the sleeve and add carbon powder, the amount of which is 1 / 9 of the sleeve volume. Place the sleeve in a heat treatment furnace and introduce nitrogen to cover the furnace. Heat the heat treatment furnace to 925°C for 20 minutes and keep warm for 30 minutes.
[0057] Quenching treatment:
[0058] After the holding time is over, the sample is immediately taken out and the end placed in the sleeve is sprayed with water for quenching. The spray water flow rate for quenching is 2L / min and the spray time is 660 seconds.
[0059] Sample cooling:
[0060] After quenching, the sample was placed in water at 23°C for cooling.
[0061] Hardness measurement:
[0062] Grinding a measuring plane on the surface of the sample along the axial direction of the sample;
[0063] On the measuring plane, the Rockwell hardness (HRC) is measured by spotting along the axial direction of the sample from the quenched end to the non-quenched end at a distance of 3 mm, 4.7 mm, 7.9 mm and 12.7 mm from the end surface of the quenched end.
[0064] The following examples and comparative examples differ from Example 1 only in the amount of carbon powder added, whether nitrogen is added, and the flow rate of spray water. Specifically, as shown in Table 3 below.
[0065] Table 3
[0066] Whether to add nitrogen Toner Addition Amount Spray water flow Example 1 <![CDATA[Add N2]]> 1 / 9 of the sleeve volume 2L / min Example 2 <![CDATA[Add N2]]> 1 / 6 of the sleeve volume 1.5L / min Example 3 <![CDATA[Add N2]]> 1 / 3 of the sleeve volume 1L / min Example 4 <![CDATA[Add N2]]> 1 / 9 of the sleeve volume 1L / min Example 5 <![CDATA[Add N2]]> 1 / 6 of the sleeve volume 2L / min Example 6 <![CDATA[Add N2]]> 1 / 3 of the sleeve volume 1.5L / min Example 7 <![CDATA[Add N2]]> 1 / 9 of the sleeve volume 1.5L / min Example 8 <![CDATA[Add N2]]> 1 / 6 of the sleeve volume 1L / min Example 9 <![CDATA[Add N2]]> 1 / 3 of the sleeve volume 2L / min Comparative Example 1 <![CDATA[Without N2]]> 1 / 9 of the sleeve volume 2L / min Comparative Example 2 <![CDATA[Without N2]]> 1 / 6 of the sleeve volume 1.5L / min Comparative Example 3 <![CDATA[Without N2]]> 1 / 3 of the sleeve volume 1L / min Comparative Example 4 <![CDATA[Without N2]]> 1 / 9 of the sleeve volume 1L / min Comparative Example 5 <![CDATA[Without N2]]> 1 / 6 of the sleeve volume 2L / min Comparative Example 6 <![CDATA[Without N2]]> 1 / 3 of the sleeve volume 1.5L / min Comparative Example 7 <![CDATA[Without N2]]> 1 / 9 of the sleeve volume 1.5L / min Comparative Example 8 <![CDATA[Without N2]]> 1 / 6 of the sleeve volume 1L / min Comparative Example 9 <![CDATA[Without N2]]> 1 / 3 of the sleeve volume 2L / min
[0067] The hardness test was performed three times for each embodiment and comparative example, and the average value data of the hardness measurement of each embodiment and comparative example is shown in the following Table 4.
[0068] Table 4
[0069] J3 J4.7 J7.9 J12.7 Example 1 45.4 42.3 36.5 27.6 Example 2 45.5 42.8 37 27.3 Example 3 45.8 43.1 36.6 27.7 Example 4 47.4 42 36.9 27.5 Example 5 45.9 40.6 34.6 27.1 Example 6 44 41.7 37.6 27.4 Example 7 44.5 42.6 37.2 27.8 Example 8 46.2 42.8 36.8 27.2 Example 9 46.4 43.9 37.7 27.3 Comparative Example 1 46.8 41.3 32.9 27.2 Comparative Example 2 46.5 40.8 33.6 27.1 Comparative Example 3 45 43.4 37.3 27.6 Comparative Example 4 47.2 43.2 35.4 27.1 Comparative Example 5 42.6 38.8 33.1 27.4 Comparative Example 6 46.1 43.8 37.8 27.8 Comparative Example 7 45.8 43.1 37.9 26.5 Comparative Example 8 45.7 43.2 36.9 27.2 Comparative Example 9 45.8 43.4 36.8 27.3
[0070] From the above Table 4, it can be seen that the test results of Examples 1-9 all meet the requirements of ASTM A255-2010(E).
[0071] By comparing and analyzing Examples 1-9 and Comparative Examples 1-9 in Table 4, it can be seen that releasing N2 gas during the furnace experiment can indeed optimize the consistency and accuracy of the end hardenability test value of SAE8620H steel, and the overall numerical reference index tends to the central value.
[0072] Comparative analysis of the other optimal examples 1, 5, 9 and control examples 1, 5, 9 in Table 4 shows that adding too much carbon powder will cause the data results to be closely biased towards the upper value, and adding too little carbon powder will cause some values to be biased towards the upper and lower limits, which are not stable enough. The amount should be added to 1 / 6 of the sleeve volume. That is, the amount of carbon powder to 1 / 6 of the sleeve volume is most conducive to improving the consistency and accuracy of the SAE8620H steel end hardenability test value.
[0073] Comparative analysis of the other optimal examples 2, 5, 8 and control examples 2, 5, 8 in Table 4 shows that under the same conditions, the automatically set spray water flow rate of 2L / min can stabilize the value at point J12.7 to the greatest extent, which indirectly shows that the spray water flow rate can affect the consistency value of the overall detection point. That is, the spray water flow rate of 2L / min is most conducive to improving the consistency and accuracy of the end hardenability test value of SAE8620H steel.
[0074] In summary, the embodiments provided in this application can improve the consistency and accuracy of the hardenability test value of SAE8620H steel. In this way, it is helpful to improve the calculation accuracy of the mathematical model and meet the calculation requirements of the hardenability of SAE8620H steel; ensure that each batch of steel produced has consistent mechanical properties and quality, improve product reliability, reduce defective rate and rework rate, reduce scrap due to quality problems, and save production costs and time. In addition, it can also reduce trial and error costs and improve production efficiency.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it; although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the relevant field should understand that the specific implementation of the present invention can still be modified or some technical features can be replaced by equivalents. Without departing from the spirit of the technical solution of the present invention, they should all be included in the scope of the technical solution claimed for protection by the present invention.
Claims
1. A method for detecting the end hardenability of SAE8620H steel, characterized in that: The following steps are involved: Prepare the test specimen; Placing the sample in a heat treatment furnace, adding nitrogen into the heat treatment furnace, wherein the nitrogen covers the entire furnace of the heat treatment furnace, and heating the sample to an austenitizing temperature; After the holding time is over, the sample is taken out from the heating furnace and subjected to water spray quenching; After quenching, the sample is placed in water for cooling; After the sample is cooled, the hardness of the quenched end of the sample is measured.
2. The method for detecting the end hardenability of SAE8620H steel according to claim 1, characterized in that: The step of placing the sample in a heat treatment furnace comprises: placing one end of the sample in a sleeve; Adding carbon powder into the sleeve, wherein the amount of carbon powder added is 1 / 7-1 / 5 of the volume of the sleeve; placing the sleeve in the heat treatment furnace; The method of water-spray quenching the sample is to water-spray quench one end of the sample placed in the sleeve.
3. The method for detecting the end hardenability of SAE8620H steel according to claim 2, characterized in that: The amount of carbon powder added to the sleeve is 1 / 6 of the volume of the sleeve.
4. The method for detecting the end hardenability of SAE8620H steel according to claim 1, characterized in that: The spray water flow rate range for water spray quenching is 1L-2L / min, and the spray time range is 649 seconds-671 seconds.
5. The method for detecting the end hardenability of SAE8620H steel according to claim 4, characterized in that: The spray water flow rate used for water spray quenching is 2L / min, and the spray time is 660 seconds.
6. The method for detecting the end hardenability of SAE8620H steel according to claim 1, characterized in that: The sample was spray quenched within 0-5 seconds after the end of the holding time.
7. The method for detecting the end hardenability of SAE8620H steel according to claim 1, characterized in that: The method for heating the sample to the austenitizing temperature is as follows: heating the heat treatment furnace to 920°C-930°C for 18-22 minutes; when the temperature in the heat treatment furnace reaches 920°C to 930°C, keeping the sample warm for 28-32 minutes.
8. The method for detecting the end hardenability of SAE8620H steel according to claim 7, characterized in that: The temperature of the heat treatment furnace is 925° C., the heating time of the heat treatment furnace is 20 minutes, and the heat preservation time of the heat treatment furnace is 30 minutes.
9. The method for detecting the end hardenability of SAE8620H steel according to any one of claims 1 to 8, characterized in that: The temperature of the water used for the sample cooling was in the range of 20°C to 25°C.
10. A method for detecting the end hardenability of SAE8620H steel according to any one of claims 1 to 8, characterized in that: The step of measuring the hardness of the quenched end of the sample comprises: Grinding a measuring plane on the surface of the sample along the axial direction of the sample; On the measuring plane, the hardness is measured at preset intervals from the quenched end to the non-quenched end along the axial direction of the sample.